Criminological Phenomenon of Illegal Placement of Indonesian Migrant Workers in Sanggau Regency - Had, Abunawas; Parulian Siagian; Muhammad Tahir; Jalil; Alfina Damayanti (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This article seeks to analyze the phenomenon of crimes against Indonesian Workers and Migrants as one of the contributions to the State in protecting its citizens. Looking at real-life conditions, it is known that crimes against workers and migrants have occurred in Indonesia, including the Sanggau Regency. The occurrence of this crime is inseparable from the use by perpetrators to benefit from the ignorance of victims, which is contrary to their dignity and human rights. The condition of victims who are pressed for economic needs also contributes to a reciprocal relationship between perpetrators and victims to be involved in Indonesian Illegal Migrant Workers and results in criminal acts of protection of labor and migrant workers. This study aims to determine the factors of the occurrence of illegal placement of Indonesian migrant workers based on criminological analysis. The method used is field research, explanatory with qualitative data collection using interviews, observations, and legal opinions that are processed descriptively with qualitative analysis. The results show the occurrence of illegal placement of Indonesian migrant workers due to weaknesses in juridical aspects that tend to be convoluted and require costs and the pragmatic thinking of victims.